Rare but Not so Rare? The Evolving Spectrum of Whipple's Disease - John M Conly; B Lynn Johnston (Canadian Journal of Infectious Diseases and Medical Microbiology)
Knowledge about Whipple's disease began to emerge in 1907, when George Hoyt Whipple recognized the first case of the disease that now bears his name. He reported the case of a 36-year-old physician with "a gradual loss of weight and strength, stools consisting chiefly of neutral fat and fatty acids, indefinite abdominal signs, and a peculiar multiple arthritis" (1). Findings at autopsy consisted of poly-serositis, aortic valve vegetations and deposition of fat in the intestinal mucosa and regional lymph nodes with marked infiltration by foamy macrophages (1). It was originally thought to be a disorder of fat metabolism, and the term 'intestinal lipodystrophy' was proposed. Whipple's disease has since been recognized as a rare, multivisceral, chronic disease with a clinical presentation dominated by a symptom triad of diarrhea, weight loss and malabsorption. However, digestive symptoms are often preceded for months or years by other symptoms, the most common being arthralgia, although cardiovascular, neurological or pulmonary involvement may be more prominent at times. Once considered the ideal case report, recent characterization of Tropheryma whippelii by means of broad range bacterial ribosomal DNA polymerase chain reaction (PCR) analysis (2,3) and its subsequent cultivation (4) has led to a veritable explosion of individual case reports, case series and hitherto unrecognized manifestations of the disease, such that it is now considered an underdiagnosed infectious disease (5). It is timely to provide an update on new developments in Whipple's disease.